These hills called home : stories from a war zone - Ao,Temsula (New Delhi : Zubaan : Penguin Books, 2006)
Based on struggle of Naga people in the Northeastern India.
Short stories.
Keywords: Naga (South Asian people); India, Northeastern; English Literature